Translation and the arts in modern France - Stephens, Sonya; Lloyd, Rosemary (Indiana University Press, 2017)
Translation and the Arts in Modern France sits at the intersection of transposition, translation, and ekphrasis, finding resonances in these areas across periods, places, and forms. Within these contributions, questions of colonization, subjugation, migration, and exile connect Benin to Brittany, and political philosophy to the sentimental novel and to film. Focusing on cultural production from 1830 to the present and privileging French culture, the contributors explore interactions with other cultures, countries, and continents, often explicitly equating intercultural permeability with representational exchange. In doing so, the book exposes the extent to which moving between media and codes--the very process of translation and transposition--is a defining aspect of creativity across time, space, and disciplines.